Morphological, chemical and growth patterns characterization in shells of Phorcus species along the northeastern coasts of Tunisia - Wafa Boulajfene; Vassiliki-Angelique Catsiki; Sabiha Tlig-Zouari (Marine and Fishery Sciences, 2024)
This work is a characterization of the morphometry, the relative growth and the metal contamination degree of the shells of two species belonging to Phorcus genus along the northeastern rocky coasts of Tunisia. The gastropods were sampled from nine locations during the winter 2017. Our findings suggested a spatial morphometric variability probably linked to the extent of the continental shelf, the coasts’ geomorphology, the dynamics of water masses, the predation and the competition effects. Furthermore, the shell investigation allowed the study of the growth pattern and indicated that the development in shell size was faster than the increase in weight. Moreover, the use of Phorcus shells as bioindicators of long-term metal contamination seems to be of growing interest, due to their abundance, high longevity, easy sampling and ecobiological features, both in a scientific and ecosystem management perspective that aims to the establishment of conservation measures targeting marine coastal environments.